Pemanfaatan Aplikasi Ruang Guru dalam Belajar di Masa Pandemi Covid-19 (Studi Kasus: Lima Orang Siswa SMA di Kota Padang) - Wahyu Dwi Yanda; Erianjoni Erianjoni (Universitas Negeri Padang, 2022)
The purpose of this study was to determine the use of Ruangguru in learning by high school students during the pandemic. In analyzing this research, the researcher uses the theory of Structural Functionalism which was developed by Robert K. Merton. The informant selection technique used is a purposive sampling technique, namely selecting informants based on the criteria determined by the number of informants 19 people. Collecting data by means of non-participatory observation, in-depth interviews and documentation. The results of research in the field found that there were 3 forms of using the Ruangguru application for high school students in Padang City: (1) Utilization of Ruangguru learning videos and quizzes, (2) Utilization of Question Banks and discussion of Questions, (3) Utilization of Ruangles Online and Roboguru features. Meanwhile, the impact of using the Ruangguru application by five high school students in the city of Padang has increased in value.